A fejlettség különböző felfogásai és mérései Európában és Magyarországon - Szabó, Pál; Farkas, Máté (Közép-Európai Közlemények, 2012)
State of development is a fundamental idea in regional policy and considerable amount of money is attached to it (financial aid for the poor countries, support for the convergence regions in the EU, etc.). For this reason the explanation and measurement of this phenomenon is essential demand. In the past years more and more approaches have been formed and this process has created serious debates. One part of it is the explanations of this phenomenon, and its connection to human development, competitiveness, standard of living, happiness etc. Another part is the measurement of the state of development: different statistical indexes and complex indicators are used to measure this phenomenon, in contrast with the GDP per capita. In this study at first the new waves are summarized shortly, thereafter the results of our researches (for Europe and Hungary) are presented. The main questions were: What kind of relations are there between the different approaches and measurements of the development? Is it practical to use the new indicators in regional policy?